Strategi Pelayanan Home care Klinik KMC Jakarta Timur dalam Menjangkau Pasien di Wilayah Padat Penduduk - Meta Mukhsinina Purnama; Purwadhi Purwadhi; Kahar Mulyani (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The increasing prevalence of chronic diseases among the elderly population necessitates the availability of routine and long-term care, making home care a relevant alternative. Home care services play a crucial role in addressing limited access to conventional healthcare facilities, particularly in densely populated and hard-to-reach urban areas. This study aims to analyze the home care service strategies implemented by Kayu Manis Medical Center (KMC) Clinic in East Jakarta to reach patients in urban settings. A descriptive qualitative approach was employed, involving seven purposively selected informants, including clinic leaders, service managers, home care coordinators, healthcare providers, administrative staff, and patients or their family members. Data were collected through in-depth interviews, participatory observation, and document review. The analysis focused on identifying service strategies encompassing cross-sectoral collaboration, optimization of accessibility through GIS-based mapping and digital platforms, strengthening human resources through training and effective communication, utilization of information technology such as Electronic Medical Record (EMR) systems, and innovations in financing schemes to improve service affordability. The findings indicate that these strategies can be comprehensively examined using the 5A framework—availability, accessibility, accommodation, affordability, and acceptability—which proved effective in enhancing the reach, quality, and acceptance of home care services. These results provide important implications for the development of community health services in urban areas, particularly in planning adaptive strategies that consider the social and geographic conditions of the population.